Severe Injuries to the Limbs Staged Treatment - Lerner, Alexander; Reis, Daniel; Soudry, Michael (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Modern weapons and high-energy accidents inflict devastating damage to soft tissue and bone. The gold standard for stabilizing high-energy fractures is immediate external fixation followed by thorough debridement of soft tissues and dead bone and irrigation, since these injuries are always grossly contaminated. The next stage of treatment - the coverage of exposed bone by vital soft tissue and definitive skeletal stabilization and reconstruction - can be a complex surgical challenge. The protocol of staged external fixation developed by the authors: primary temporary unilateral tubular stabilization followed by definitive circular Ilizarov (hybrid) fixation, is outlined and comprehensively described in this book. The text provides guidelines for the young surgeon as well as the senior orthopedic trauma surgeon in staged definitive limb functional reconstruction. The rationale and advantages of a logical progression of surgical steps are explained and fully illustrated throughout, drawing from an archive of clinical photographs and X-ray documentation covering all steps of the treatment protocol in a large variety of complex cases, including extensive bone and soft tissue loss. This practical guide is based on the accumulated experience of 40 years in the treatment of severe injuries of the musculoskeletal system with grave tissue loss, and in particular war injuries. Emphasis is given to the proper attention and care of the soft tissues, sequential damage control, and the judicious staged use of appropriate external fixation.